Mineralogical characterization of clays used in the structural ceramic industry in west of S. Paulo State, Brazil - Teixeira,S. R. (2001)
Plasticity and the grain-size distribution of the raw material used to make structural bricks and roof tiles are very important to the production process. These two parameters and the mineral composition will define the quality and properties of the final product: color, mechanical resistance, water absorption, cracks, swell and shrink during drying and firing the ceramic pieces etc. In the Brazilian ceramic industry it is very common to mix together two or more different kinds of raw material to achieve the ceramic mass with the desired grain-size distribution. The objective of this work was to characterize the raw material collected at the floodplains of the Paraná and Paranapanema Rivers and the ceramic mass used by the ceramic industry in western São Paulo State, Brazil. Particle size distribution, organic matter and X-ray diffraction were used to study this material. The textural analysis indicates that the raw materials have the clay fraction ranging from 38.2% to 66.3%, the silt from 22.2% to 49.7% and the sand from 3.1% to 34.1%. The results indicate that all mixed raw materials have more clay in its composition than would be necessary. The organic matter ranges from 5 to 7%. All samples have kaolinite and many of them have smectites, HIV and mica. Gibbsite, iron and titanium oxides, and quartz are also identified. One of the samples (yellow) is rich in goethite.